TOTAL MIKROBIA JAMU SERBUK KEMASAN DAN TANPA KEMASAN PRODUK BANJARMASIN - Ratih Indah Sari; Sri Sinto Dewi; Wildiani Wilson (Poltekkes Kemenkes Pakassar, 2020)
Traditional powder herbs is a heritage from Indonesia used for medication. Requirements of traditional powder herbs are secure, good quality and useful. To keep quality so that it is not contain microbial. This study aims is to know total of microbial on packaging and without packaging herbs production of Banjarmasin. Method which is used is observational analytic. Samples in this study are packaging and without packaging herbs production of Banjarmasin. Counting total of microbial uses Total Plate Count method. The average total microbial of packing herb sample is 58.90%, while the average total microbial of packaging herb sampel is 65.20%. Data was analyzed using Mann Withney test and the result is 0,462 with p value <0,05 so there is no significan correlation between packaging herb total microbial. Keywords : Microbes, Non Packaging, Packaging herbs